Refinement of the Protein Immunomarking Technique for Mark-Capture Research. Issue 2 (19th March 2020) - Hagler, James R; Machtley, Scott A
Abstract: A follow-up study was conducted to further evaluate the marking efficiency of broadcast spray applications of egg albumin (from chicken egg whites) on Hippodamia convergens Guérin-Méneville (Coleoptera: Coccinellidae) in alfalfa. A previous study recorded exceptional marking efficiency (e.g., >95% of the population) on H. convergens when using relatively high concentrations (10 to 50%) of chicken egg whites. The present study examines marking efficiency of egg whites using lower concentrations of 2.5, 5.0, and 10.0%. We used cadaver and free-roaming beetles to measure protein mark acquisition (and retention) of each protein concentration by direct contact with the spray application and incidental contact with protein residue on the plant tissue, respectively. The vertical distribution of the protein mark was also determined by sampling the upper and lower portions of the alfalfa canopy. The data indicate, regardless of the egg white treatment, that the backpack sprayer provided uniform coverage of egg albumin on the alfalfa plants and cadaver beetles. Also, almost every free-roaming beetle acquired a mark within 24 h after contact exposure to protein marked plants. This study shows that a very low concentration of egg albumin is sufficient for marking arthropods directly in the field.